Community Empowerment Through Tourism Development in East Kalimantan - Aji Ratna Kusuma (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
The tourism sector is the government's mainstay sector in development because this sector experiences rapid development every year so that it can increase the country's foreign exchange, local revenue, absorb many jobs and generate other economic sectors. This study uses the Mix Method model with a case study approach in three sample areas. Data analysis uses Qualitative Data Software Analysis NVivo12 Plus, with the aim of describing tourism development that is determined and regulated by the government through laws and regulations providing an overview of community involvement in many things such as eradicating poverty which will ultimately improve people's welfare and increase economic growth. Community empowerment through the Enabling, Empowering and Protecting model is a combination of approaches taken by the government and the community, starting from making regulations as a basis for accommodating community potential, opening up opportunities so that people are increasingly empowered to become the subject of development to protecting policies and involving various private companies through the Corporate Social program. Responsibility and active involvement of MSMEs